Microfluidic bubble generation by acoustic field for mixing enhancement - Wang, Shasha (2013)
We demonstrate the bubble generation in a microfluidic channel by both experimental observation and numerical simulations. The microfluidic channel contains a nozzle-shaped actuation chamber with an acoustic resonator profile. The actuation is generated by a piezoelectric disk below the chamber. It was observed that for a steady deionized (DI) water flow driven through the channel, bubbles occurred in the channel when the piezoelectric disk was actuated at frequencies between 1 kHz and 5 kHz. Outside this actuation frequency range, no bubble generation was observed in the channel. The experiment showed that the presence of bubbles in this frequency range could significantly enhance the fluid mixing in the microfluidic channel, which otherwise would not happen at all without the bubbles. To further understand the bubble generation, the flow field in the microchannel was numerically simulated by a two-dimensional model. The numerical results show that there is a low pressure region inside the actuation chamber where water pressure is below the corresponding vapor pressure and thus bubbles can be generated. The bubble generation was also experimentally observed in the microchannel by using a high speed camera.